Jejunal diverticulitis: An unusual cause of left lower quadrant abdominal pain in a young female - Chandrashekhar A Sohoni (Muller Journal of Medical Sciences and Research, 2014)
Acquired small bowel diverticulitis is an uncommon condition, predominantly affecting elderly population. It is exceedingly rare in young adults. Such a rare case of jejunal diverticulitis in a young female is presented here. Due to the nonspecific clinical presentation, accurate clinical diagnosis of this condition is difficult. Computed tomography (CT) scan provides early and specific diagnosis, thus facilitating successful nonsurgical treatment.